Varicella-Zoster Virus Encephalitis in an Immunocompetent Adult with Disseminated Cutaneous Herpes Zoster after Testosterone Booster Supplements: Case Report - Ghada Alhayaza; Abdullah Al-Omair; Hind M. Almohanna (Karger Publishers, 2022)
Disseminated zoster affects immunocompromised individuals and has a nondermatomal distribution. We report a 28-year-old male who initially presented to the dermatology clinic with pinprick sensation over the right side of his face that was followed by vesicular eruption. Upon which he was diagnosed with herpes zoster and discharged on topical mupirocin ointment three times a day for 7 days and valacyclovir 1 g oral three times a day. A few hours later, he presented to the emergency department with drowsiness and an episode of loss of consciousness. He was then admitted by neurology and found to have herpetic encephalitis. During admission, he was started on intravenous acyclovir 10 mg/kg three times a day. After 3 weeks of intravenous acyclovir, the patient improved clinically; and all the vesicular lesions have crusted. Up to this date, there are only a few cases of immunocompetent adult patients with disseminated cutaneous herpes zoster (DCHZ), most of whom were over the age of 65 years or taking immunosuppressive medication. We report a case of DCHZ and varicella-zoster virus encephalitis in a young immunocompetent patient using daily testosterone supplements and a history of emotional and physical stress, in contrast to all previously reported cases, which presented significant risk.